INKONSISTENSI BATAS USIA DEWASA DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Muhammad Bahram (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the inconsistency in determining the legal age of majority within various Indonesian laws and regulations and to examine its implications for legal certainty within the national legal system. The research problem arises from the existence of different standards of legal adulthood in several regulations, particularly between provisions that set the age at nineteen years and others that still recognize twenty-one years as the threshold of legal maturity. This research employs a normative legal research method using statutory and conceptual approaches supported by literature studies of relevant primary and secondary legal sources. The findings indicate that the differences in determining the age of majority are influenced by historical factors in legislative development, the varying regulatory objectives across legal sectors, and the lack of optimal harmonization among laws and regulations. Such conditions may create potential legal uncertainty in the application of law, particularly when determining an individual’s legal capacity to perform legal acts. Therefore, this study emphasizes the importance of harmonizing regulations concerning the age of majority to establish a more consistent legal system, strengthen legal certainty, and support the development of more coherent national legal policies